2021
DOI: 10.1016/j.heliyon.2021.e07214
|View full text |Cite
|
Sign up to set email alerts
|

Undergraduate health profession students attitudes toward illicit substance users in Jordan

Abstract: Background The use of illicit substances is a critical international issue that must be addressed by healthcare systems worldwide. Today, the problem of illicit substance use is increasingly becoming a burden on healthcare systems in both developed and developing countries. The aims of this study were: (1) to describe the attitudes of health major undergraduate students (the study participants) toward illicit substance users; (2) to describe the discriminatory behaviors among the study participant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
(57 reference statements)
0
2
0
Order By: Relevance
“…These studies examined factors that affect the attitudes of practicing HCPs toward those who abuse substances. Only few studies examined the attitude of emerging HCPs to those with SUD, and that too not in the recent years [ 8 , 10 ]. Data from the U.S. reveal that the number of people with SUD is on the rise [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These studies examined factors that affect the attitudes of practicing HCPs toward those who abuse substances. Only few studies examined the attitude of emerging HCPs to those with SUD, and that too not in the recent years [ 8 , 10 ]. Data from the U.S. reveal that the number of people with SUD is on the rise [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Personal characteristics can impact one's attitude toward those with SUD. Few studies have shown that gender, education, income, knowing a drug abuser, and previous personal experience with substance users are factors that influence the HCP's attitudes and discriminatory behaviors toward those who abuse substances [6][7][8][9]. These studies examined factors that affect the attitudes of practicing HCPs toward those who abuse substances.…”
Section: Introductionmentioning
confidence: 99%